Breast and axilla conserving surgery in the management of eary-stage breast cancer - Blichert-Toft, Mogens (Radiology and oncology (Ljubljana), 2000)
The main incentive to breast conserving therapy (BCT) relates to preserving femininity and avoiding the feeling of female inferiority and a disfigured body image. Some women are even more concerned about preserving the breast rather than preserving life. The preconditions for BCT are satisfactory cosmesis, good physical function, and loco-regional disease control. If the breast is badly disfigured following BCT there is little sense in breast conservation. The mainstay of early-stage breast cancer treatment is surgery. One option is breast conservation in case of eligibility. Radicality of the surgical procedure is emphasized wheter mastectomy or breast conservation has been undertaken. Risk factors related to BCT in particular arescritinized, andespecially young age and extensive ductal components of the specimen are dealt with as independent risk factors for local control in BCT. BCT in Denmark amounts to about 30% of operations in breast cancer. This is a rather low frequency compared with figures from other countries. Consequently, the Danish eligibility criteria are discussed. The reasons for axillary dissectionare emphasized. Even in small tumours below 10 mm, axillary nodes. The introduction of the sentinel node principle seems to provide a basis for conservation of healthy axillary lymph nodes in node negative patients.
Keywords: Axilla; Breast neoplasms; dojke; kirurško zdravljenje; Lymph node excision; Mastectomy; rak (medicina); Self concept; Surgery